ANALISIS DETERMINAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS MAKRAYU KOTA PALEMBANG TAHUN 2023 - Yuniartina; Nani Sari Murni; Gema Asiani; Arie Wahyudi (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2023)
Background: Makrayu Community Health Center data for 2022, 98% of household heads with access to proper sanitation facilities (healthy latrines), 94.96% of residents with sustainable access to quality (proper) drinking water and households washing hands with soap (CTPS) is 96%. Diarrhea is a condition in which individuals experience an increase in the frequency of defecation three or more times a day accompanied by changes in the concentration of stool in liquid form with or without mucus or blood. The incidence of diarrhea can be seen from the use of clean water supply, provision of family latrines, provision of landfills and provision of waste water disposal. This study aims to find out the analysis of the determinants of the incidence of diarrhea in toddlers in the working area of ​​the Makrayu Public Health Center, Palembang City in 2023. Methods: The study design was case control. The population in the study were diarrhea patients in toddlers in the Working Area of ​​the Makrayu Health Center as many as 245 toddlers. The sample in the study amounted to 71 toddlers. The sampling technique used proportional random sampling and continued with purposive sampling. Data collection was carried out on June 5-21, 2023. The research instruments were questionnaires and observation sheets. Bivariate analysis used the chi-square test, while multivariate analysis used multiple logistic regression tests. Results: The results of the bivariate analysis showed that there was a relationship between knowledge (p value 0.032), attitude (p value 0.016), Stop BABs (p value 0.000), CPTS (p value 0.000) and PSRT (p value 0.002), while there was no relationship between PAM- RT (p value 0.116) with diarrhea as a determinant. The results of multivariate analysis showed that the dominant factor determining the incidence of diarrhea was household waste management (p value 0.003; OR= 0.171). Conclusion: Based on the results of the research, it is hoped that it will increase knowledge by means of public health counseling and seminars, especially regarding the incidence of diarrhea, such as continuing to provide education to the public in protecting the environment so that they are protected from various types of diseases, especially diarrhea. Keywords: Diarrhea, Incidence, Toddlers